WHAT IS THE ROLE OF THE MODERN POET ? - Homsley, Dr. Bonnie (مجلة كلية الاداب, 1973)
The question of the poet's role is a problem that thinkers from Plato and Aristotle down to the present moment have dealt with, and no one person has made the final statement. Though this essay is restricted insubject to contemporary British and American poets, it is vital to define the nature of poetry and the artist in general before proceeding with particular poets. The artist is a creative maker whose product is a work of art, which in turn creates the transcendental effect of beauty. The work of art is born in matter with form by an incarnated mind, with the mental conception of the poem as the germ or embryo. The finished product perfect only when the work is fully formed or born. Art must be viewed as an end in itself. All practical concerns such as providing knowledge or teaching morals are secondary. The primary function of poetry is to create beauty. Poetry must first be musical and should combine words and rhythm into a coherent order. Emotions and attitudes as expressed in Images symbola, figures of speech, and musical techniques mich prosody, onamatopoesis, and alliteration are central to the creation and total experience of poetry.